Body Mapping As Risk Factors For Non-Communicable Disease In East Borneo - Jadid, Muhamad Ar-Ruhul; Ariyanti, Rea (Universitas Mulawarman, 2025)
Non-communicable diseases (NCDs), particularly hypertension, pose a significant health concern in East Kalimantan, with a national prevalence of 34.1% among individuals aged ≥ 18 years. The underutilization of spatial data frequently gives rise to interventions that are not targeted with optimal precision. The objective of this study is to map the incidence of hypertension and its risk factors in 10 districts/cities in East Kalimantan Province. This study employs a descriptive approach to investigate the prevalence of hypertension and its associated risk factors. The data were collected from the Indonesian Healthy Application for Non-Communicable Diseases (ASIK) program. The sample in this study consisted of all 10 districts/cities in East Kalimantan Province that have implemented the ASIK NCD information system program in 2024. The analysis was conducted using descriptive methods and presented in the following forms: narrative, tabular, and mapping. These data were analyzed using the QGIS application. The analysis revealed that the highest prevalence of hypertension was observed in Penajam Paser Utara (36.5%) and Samarinda (36.0%), while the largest absolute case burden was identified in Kutai Kartanegara (84,335 individuals). The analysis revealed significant disparities in risk factors, with Mahakam Ulu District exhibiting predominance in nearly all domains, including insufficient physical activity (70.7%), alcohol consumption (25.5%), obesity (34.5%), and smoking (22.7%). In conclusion, the distribution of hypertension in East Kalimantan is fairly even, but it is driven by different risk determinants across regions. This makes it challenging to implement uniform prevention strategies.